Development and validation of the atopic dermatitis and infant skincare knowledge, attitude, and practice (ADISKAP 1.0) scale - Xiaoyan Sun; Mutong Zhao; Qiong Wu; Jing Tian; Chunping Shen; Yuan Liang; Shan Wang; Lei Jiao; Yang Wang; Mingyi Liu; Lin Ma; Xiuhua Ma (Wiley, 2023)
ABSTRACT Importance Preserving skin health is crucial for atopic dermatitis control as well as for the thriving of children. However, a well‐developed and validated tool that measures the knowledge, attitude, and practice of skin care is lacking. Objective To develop and validate the atopic dermatitis and infant skincare knowledge, attitude, and practice (ADISKAP 1.0) scale that measures parental health literacy on atopic dermatitis and skin care. Methods We conducted a review of the literature, a focus group (two dermatologists and 12 parents), and a panel discussion in order to generate the ADISKAP prototype. Two samples of parents with knowingly superior (dermatologists, n = 59) and inferior (general population, n = 395) knowledge traits participated in the validation of ADISKAP. Cronbach's alpha was reported as a measure of internal consistency, and the intraclass correlation coefficient (ICC) was calculated to assess the test‐retest validity. The known‐groups technique was used to evaluate construct validity. Results The ADISKAP scale contained 17 items after content and face validity validation. After removing items that displayed poor test‐retest reliability (n = 4) and construct validity (n = 3), 12 items were retained in the ADISKAP 1.0. Interpretation ADISKAP 1.0 is a reliable and valid tool for assessing parental knowledge, attitude, and practice on infantile atopic dermatitis and skin care.